OPTIMIZATION OF PUBLIC RELATIONS MANAGEMENT IN INCREASING BRANDING AND ATTRACTIVENESS OF ISLAMIC EDUCATION INSTITUTIONS - Afidah, Briliana (Universitas Nurul Jadid, 2024)
This study focuses on optimizing the role of public relations in building the branding of state Islamic high schools and its impact on public interest. The purpose of this study is to analyze strategies that can be applied by public relations to strengthen the branding of Islamic high schools and increase public interest. The research method used is a qualitative approach with a descriptive research type. Data collection techniques include directed interviews, observation, and documentation. Data analysis is carried out through interactive data analysis techniques that include data reduction, data presentation, and conclusions. The results of the study indicate that the optimal role of public relations, supported by the quality of human resources, effective promotion, good communication, and adequate facilities, can significantly increase the branding of Islamic high schools and attract public interest. The integration of technology in promotional strategies has also proven to be a key factor in the digital era. The implications of this study provide insight for other Islamic educational institutions to develop effective branding strategies to increase their appeal and reputation in the eyes of the public.